2017
DOI: 10.1177/1474704917711513
|View full text |Cite
|
Sign up to set email alerts
|

Your Cheatin’ Voice Will Tell on You: Detection of Past Infidelity from Voice

Abstract: Evidence suggests that many physical, behavioral, and trait qualities can be detected solely from the sound of a person's voice, irrespective of the semantic information conveyed through speech. This study examined whether raters could accurately assess the likelihood that a person has cheated on committed, romantic partners simply by hearing the speaker's voice. Independent raters heard voice samples of individuals who self-reported that they either cheated or had never cheated on their romantic partners. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Across studies, we examined potential mediators of any accuracy in unfaithfulness judgments, chosen based on previous studies. These included perceptions of attractiveness, as people may infer that more attractive individuals will have more opportunity to be unfaithful, and perceptions of masculinity, which is a valid cue to unfaithfulness in men [ 10 , 25 ]. We also included untrustworthiness judgments, to confirm that accuracy is specific to unfaithfulness, as found in previous studies [ 9 , 10 ], rather than reflecting more general impressions of untrustworthiness.…”
Section: Introductionmentioning
confidence: 99%
“…Across studies, we examined potential mediators of any accuracy in unfaithfulness judgments, chosen based on previous studies. These included perceptions of attractiveness, as people may infer that more attractive individuals will have more opportunity to be unfaithful, and perceptions of masculinity, which is a valid cue to unfaithfulness in men [ 10 , 25 ]. We also included untrustworthiness judgments, to confirm that accuracy is specific to unfaithfulness, as found in previous studies [ 9 , 10 ], rather than reflecting more general impressions of untrustworthiness.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology undertaken in this research is similar to the methodology undertaken by Hughes and Harrison [19], Imhof [35] and Smith et al [36]. Participants were informed about the study procedure and given the option to opt out of the online survey at any point of time.…”
Section: Methodsmentioning
confidence: 99%
“…In [19] it is noted that pitch has a small role in detecting cheating probability of infidelity among committed romantic partners, but it does not represent the entire picture. Hughes and Harrison [19] did not consider other acoustical measures or any combination of different acoustic measures in the research.…”
Section: Background and Related Workmentioning
confidence: 99%
“…One such example of user affect could potentially be trust. [36] has observed the likelihood that an individual has cheated on committed, romantic partners simply by hearing 10 seconds the speaker's voice. In addition to comparing the original voice samples of male and female voices against each other, they also manipulated the pitch of the voice samples to identify and link between the difference in pitch and the likelihood of cheating.…”
Section: Related Workmentioning
confidence: 99%
“…They also observed that both males and females with a manipulated lower pitch had higher cheating ratings than those with manipulated higher pitch. As [36] noted, pitch does play a role in detecting infidelity, but it does not represent the entire picture, since raters were still able to identify cheaters by only using very thin slices of vocal information.…”
Section: Related Workmentioning
confidence: 99%